1999
DOI: 10.2466/pr0.1999.85.3.883
|View full text |Cite
|
Sign up to set email alerts
|

Children and Electronic Games: A Comparison of Parents' and Children's Perceptions of Children's Habits and Preferences in a United States Sample

Abstract: Despite the popularity of violent electronic games, anecdotal evidence suggests that many parents lack even basic information about children's game-playing habits. The goal of the present study was to examine parental knowledge of children's electronic game-playing habits by assessing the congruence between children's and parents' perceptions of child's playing time, parental supervision, game preference, and reaction to actual game-playing. 35 children in Grades 3 to 5 and one parent of each child completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 10 publications
1
13
0
1
Order By: Relevance
“…(Parents were not always up-to-date on what their children had been exposed to [5].) There were also a couple of boys who knew the Sneakers game.…”
Section: Participantsmentioning
confidence: 97%
“…(Parents were not always up-to-date on what their children had been exposed to [5].) There were also a couple of boys who knew the Sneakers game.…”
Section: Participantsmentioning
confidence: 97%
“…Children daily life is something that children know the most about. Studies have found that parents do not really know how children spend their time (Funk et al, 1999) or what they are worried about (Gottlieb and Bronstein, 1996) . Hence to answer such questions in the best possible way we need the children to be involved in the studies, at least as our primary source of information.…”
Section: The Consequences Of the Changing Fieldmentioning
confidence: 98%
“…Therefore, it could be speculated that any video game, independent of the violent content, could produce frustration. However, a study by Funk et al [1999] found that those who played a violent video game (Terra Nova) reported significantly higher frustration levels than those playing a non-violent video game (Marble Drop). 2 Kirsh et al [2005] found a significant main effect for gender such that women were more frustrated with video games than men, suggesting that frustration should be a covariate.…”
Section: What Influences Aggressionmentioning
confidence: 99%